(untitled) (Journal of Economic Research & Business Administration, 2016)
In the current conditions of the market economy of developed and developing countries small and medium business is recognized to be a reliance of achieving economic growth, welfare of population. Since Kazakhstan has gained its independence and moved to market relations one of the main tasks is to support small and medium businesses and entrepreneurship. The increase of the share of small and medium businesses, developing entrepreneurship is prosperity of the country and improvement of socio-economic status of people. In order to achieve such situation there are all the opportunities in the country as evidenced by the results obtained in the present. As a proof of it we can consider the program «Business Road Map 2020» adopted by the Government in 2010 and aimed to develop entrepreneurship of the country. It is said there that the national economy can be improved by development of employment and improvement of the socio-economic situation of the population, introduction of scientific and technical innovations through development of entrepreneurship, small and medium businesses.